Effect of high-pressure processing applied as pretreatment on carotenoids, flavonoids and vitamin C in juice of the sweet oranges 'Navel' and the red-fleshed 'Cara Cara'. (June 2020) - De Ancos, Begoña; Rodrigo, María J.; Sánchez-Moreno, Concepción; Pilar Cano, M.; Zacarías, Lorenzo
Graphical abstract: Highlights: HPP on peeled Navel orange fruit increased flavonoids, phythoene and phytofluene in juices. HPP-Cara Cara juices have higher carotenoid content than HPP-Navel juices. HPP preserved flavonoids and vitamin C but decreased lycopene in Cara Cara juices. Carotenoids structure and deposition in food matrix modulate the effect of HPP. Abstract: This work examines the effect of HPP at 200 MPa/25 °C/1 min (HPP-200) as pretreatment on whole-peeled orange fruits from ordinary 'Navel' and red-fleshed 'Cara Cara' sweet oranges before juicing with the aim to improve the extractability of carotenoids, flavonoids, vitamin C and hydrophilic antioxidant activity in the juices. Untreated and HPP-200 juices were subsequently processed at 400 MPa/40 °C/1 min (HPP-400 and HPP-200-400). HPP-200 and HPP-200-400 increased the concentration of hesperidin (25% and 16%), narirutin (27% and 9%), phytoene (40% and 97%) and phytofluene (9- and 12-fold) in Navel-juice and maintained the vitamin C content and the antioxidant activity compared to untreated freshly-prepared juice. However, these two HPP treatments in Cara Cara-juices preserved flavonoids and vitamin C concentration but decreased 16% total carotenoid content mainly lycopene due to its more exposed position in the food matrix. However, a single HPP-400 treatment applied on freshly-prepared orange juices reduced bioactive compounds, mainly in Navel-juices, perhaps due to the mechanical juicing procedure (jar-blender) used or/and with the pressure-induced activation of detrimental food enzymes. All the HP-treated Cara Cara-juices presented higher carotenoid content than the corresponding Navel-juices, and can be considered an excellent dietary source of these compounds. Therefore, HPP applied to whole peeled orange did not modified the profiling of bioactive compounds of Navel- and Cara Cara-juices and increased the concentration of total and individual carotenoids, flavonoids, vitamin C and antioxidant activity depending on the type of bioactive compounds, the orange fruit cultivar and the HPP conditions.